Dark Silicon and the End of Multicore Scaling - Esmaeilzadeh, Hadi; Blem, Emily R.; St. Amant, Renee; Sankaralingam, Karthikeyan; Burger, Doug (IEEE Micro, 2012)
A key question for the microprocessor research and design community is whether scaling multicores will provide the performance and value needed to scale down many more technology generations. To provide a quantitative answer to this question, a comprehensive study that projects the speedup potential of future multicores and examines the underutilization of integration capacity-dark silicon-is timely and crucial.